A "Prime-Pull" Vaccine Strategy Has a Modest Effect on Local and Systemic Antibody Responses to HIV gp140 in Mice - Tregoning,JS; Buffa,V; Oszmiana,A; Klein,K; Walters,AA; Shattock,RJ (PLOS One, 2013)
One potential strategy for the prevention of HIV infection is to induce virus specific mucosal antibody that can act as animmune barrier to prevent transmission. The mucosal application of chemokines after immunisation, termed ‘‘prime-pull’’,has been shown to recruit T cells to mucosal sites. We wished to determine whether this strategy could be used to increaseB cells and antibody in the vaginal mucosa following immunisation with an HIV antigen. BALB/c mice were immunisedintranasally with trimeric gp140 prior to vaginal application of the chemokine CCL28 or the synthetic TLR4 ligand MPLA,without antigen six days later. There was no increase in vaginal IgA, IgG or B cells following the application of CCL28,however vaginal application of MPLA led to a significant boost in antigen specific vaginal IgA. Follow up studies toinvestigate the effect of the timing of the ‘‘pull’’ stimulation demonstrated that when given 14 days after the initialimmunisation MPLA significantly increased systemic antibody responses. We speculate that this may be due to residualinflammation prior to re-immunisation. Overall we conclude that in contrast to the previously observed effect on T cells, theuse of ‘‘prime-pull’’ has only a modest effect on B cells and antibody.